2001
DOI: 10.1002/1521-3846(200108)21:3<207::aid-abio207>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Bacteria from Different Wastewater Treatment Plants

Abstract: The surface properties of the individual members of degradative biocommunities isolated from different laboratory and natural populations were characterized. The bacterial strains isolated from a given origin and degrading a given substrate varied with respect to their hydrophobic and electrostatic properties (e.g. contact angle, adsorption to hexadecane, isoelectric point, adsorption of anionic or cationic dyes). However, despite their specific surface characteristics, in most cases the net charge properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Only a marginal variation in IEP was observed in the presence of the chemical surfactants, i.e., the IEP range was 2.3-2.6 for B. cepacia (ES1) and 2.0-2.7 for B. multivorans (NG1). Martienssen et al (2001) reported the IEP of several bacterial cultures isolated from wastewater treatment plants to be in the range of 3-3.8. Van der Wal et al (1997) reported the IEP of five Gram-positive bacterial cultures which were also in the above range, except Rhodococcus erythropolis A177, which demonstrated an IEP ≤2.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a marginal variation in IEP was observed in the presence of the chemical surfactants, i.e., the IEP range was 2.3-2.6 for B. cepacia (ES1) and 2.0-2.7 for B. multivorans (NG1). Martienssen et al (2001) reported the IEP of several bacterial cultures isolated from wastewater treatment plants to be in the range of 3-3.8. Van der Wal et al (1997) reported the IEP of five Gram-positive bacterial cultures which were also in the above range, except Rhodococcus erythropolis A177, which demonstrated an IEP ≤2.0.…”
Section: Discussionmentioning
confidence: 99%
“…At 60 h (log growth phase), the zeta potential in the presence of varying doses of Triton X-100 was less electronegative compared to that at 36 (mid-log) and 168 h (stationary phase). The net charge on the cell surface is a result of interaction of functional groups present on the cell surface, and since presence/abundance of these groups is metabolically regulated (Martienssen et al 2001), some variation may be expected over the growth phase.…”
Section: Alteration In Csh and Zeta Potential During Surfactant-aidedmentioning
confidence: 99%
“…This charge on cell surface is a result of an interaction of functional groups present on microorganisms' cell surface. Furthermore, the presence or abundance of these groups is metabolically regulated (Marienssen et al, 2001). The presence of a surfactant in the system can lead to an alteration in cell surface functional groups.…”
Section: Effect On Zeta Potentialmentioning
confidence: 99%
“…The microbes are different in their size, shape and in the composition of the outer membranes, which include the large number of lipids, proteins, etc. The isoelectric points, pI's, of microbes [3] are more appropriate parameters than the electrophoretic mobilities; pI's are practically independent from the measurement conditions [4,5]. Several papers were published showing the successful separation of microorganisms according to their pI by capillary isoelectric focusing (CIEF) [1,5,6].…”
Section: Introductionmentioning
confidence: 99%